Why Student Aid Matters? Roadblocks to the Transition into Higher Education for Forced Migrants in Chile - Blanco, Christian; Meneses, Francisco; Villamizar-Chaparro, Mateo (World Bank, Washington, DC, 2022)
Education is a powerful tool for social mobility and cultural integration. However, it is one of the largest hurdles for migrants—particularly for forcefully displaced migrants, given their more vulnerable condition and lack of resources to pay for private education. This paper explores educational gaps between migrants and natives in Chile, a country that provides free public education to newcomers. The paper analyzes an administrative data set that includes all students in the Chilean educational system and follows students from 2017 to 2018. Using a research discontinuity design around the cut-off for financial aid to tertiary education, this paper investigates whether access to financial aid generates incentives for forced migrants to enroll in tertiary education. This research confirms previous findings that show that migrants have lower advancement and enrollment rates than natives at every school level. Moreover, it finds that financial aid applications constitute a major roadblock preventing migrant students from accessing higher education. Furthermore, the paper presents suggestive evidence showing that the interaction between the type of school (vocational vs. technical) and the migrant condition affects applications for financial aid.